Managing political risks in European MNEs’ R&D activities in China - Tuomaala, Eveliina (My University, 2026)
Recent geopolitical crises and tensions, such as the war in Ukraine and rising tensions between the U.S. and China, along with intensifying technological competition and the pursuit of technological sovereignty, have significantly undermined R&D internationalization. At the same time, many of the world’s most pressing challenges, such as climate change, cannot be solved by individual firms alone, underscoring the continued importance of international R&D collaboration. Over the course of the 21st century, China has evolved into a distinctive innovation ecosystem, offering compelling incentives for foreign MNEs to conduct R&D activities in the country. However, alongside similar developments in the U.S. and the EU, there are indications that China is increasingly shielding its R&D system from the rest of the world. European MNEs report rising political challenges, including weak IPR protection, an unequal playing field for foreign firms, and limited or non-existent government support. At the same time, European MNEs face significant geopolitical concerns in their R&D activities in China, including the U.S.-China technology rivalry and the risk of a potential conflict in the Taiwan Strait. Consequently, effective risk management and identifying ways to mitigate political risks have become essential for European MNEs. Recognizing the limited understanding in existing literature regarding the impact of politics and geopolitics on R&D internationalization, as well as the growing need to manage political risks in international R&D activities in China, the aim of this study is to investigate how foreign MNEs can manage political risks in their R&D activities in China. The research employs a qualitative research approach, with empirical data collected through semi-structured expert interviews with eight professionals representing organizations from both the public and private sectors. The findings show that foreign MNEs are driven to conduct R&D activities in China by a range of market-, knowledge-, government-, and risk mitigation-related benefits. However, these activities also involve substantial political risks. These risks originate from both internal and external sources, with external risks, such as home-host country relations and broader geopolitical dynamics, shaping and intensifying internal political risks. Geopolitical risks, in particular, are found to have a significant impact on European MNEs’ R&D activities in China amid rising geopolitical tensions, conflicts, and techno-nationalism. Nevertheless, the findings also demonstrate that foreign MNEs can employ a variety of strategies, measures, and tools to mitigate these risks, among which political capabilities emerge as especially important. Moreover, the home country, industry, and other firm-specific characteristics influence both the severity and the manageability of political risks, leaving some firms better positioned than others to cope with them. This study contributes to the academic literature by providing new insights into how politics and geopolitics shape R&D internationalization, why some firms continue to engage in international R&D activities in countries characterized by substantial political risks, and how firms can respond to political disruptions affecting their R&D activities. In addition, the study offers practical value by helping companies identify key political risks associated with international R&D activities in China and by illustrating concrete strategies, measures, and tools through which these risks can be mitigated.

Viimeaikaiset geopoliittiset kriisit ja jännitteet, kuten Ukrainan sota ja kasvavat jännitteet Yhdysvaltojen ja Kiinan välillä, sekä kiristynyt teknologinen kilpailu ja pyrkimykset teknologiseen suvereniteettiin ovat merkittävästi heikentäneet kansainvälistä T&K-toimintaa. Samanaikaisesti monet maailman polttavista haasteista, kuten ilmastonmuutos, eivät ole yksittäisten yritysten ratkaistavissa, mikä korostaa kansainvälisen T&K-yhteistyön jatkuvaa merkitystä. 2000-luvun aikana Kiina on kehittynyt omaleimaiseksi innovaatioekosysteemiksi, joka tarjoaa merkittäviä kannustimia ulkomaisille monikansallisille yrityksille harjoittaa T&K-toimintaa maassa. Samanaikaisesti, Yhdysvalloissa ja Euroopan unionissa tapahtuneiden kehityskulkujen ohella, on viitteitä siitä, että Kiina suojaa yhä enemmän T&K-järjestelmäänsä muulta maailmalta. Eurooppalaiset monikansalliset yritykset raportoivat kasvavista poliittisista haasteista, kuten heikosta immateriaalioikeuksien suojasta, epätasaisista toimintaedellytyksistä ulkomaisille yrityksille sekä rajallisesta tai olemattomasta valtiontuesta. Lisäksi eurooppalaiset monikansalliset yritykset kohtaavat merkittäviä geopoliittisia huolenaiheita T&K-toiminnassaan Kiinassa, mukaan lukien Yhdysvaltojen ja Kiinan välinen teknologinen kilpailu sekä mahdollisen konfliktin riski Taiwanin salmella. Tämän seurauksena tehokas riskienhallinta ja poliittisten riskien lieventämiskeinojen tunnistaminen ovat nousseet keskeisiksi eurooppalaisille monikansallisille yrityksille. Tunnistaen kirjallisuudessa vallitsevan rajallisen ymmärryksen politiikan ja geopolitiikan vaikutuksista kansainväliseen T&K-toimintaan sekä kasvavan tarpeen hallita poliittisia riskejä kansainvälisessä T&K-toiminnassa Kiinassa, tämän tutkimuksen tavoitteena on selvittää, miten ulkomaalaiset monikansalliset yritykset voivat hallita poliittisia riskejä T&K-toiminnassaan Kiinassa. Tutkimuksen empiirinen osio on toteutettu laadullisilla puolistrukturoiduilla asiantuntijahaastatteluilla, joihin osallistui kahdeksan julkista ja yksityistä sektoria edustavaa asiantuntijaa. Tutkimuksen tulokset osoittavat, että ulkomaisia monikansallisia yrityksiä ohjaavat T&K-toimintaan Kiinassa useat markkinoihin, osaamiseen, hallintoon ja riskienhallintaan liittyvät hyödyt. Samanaikaisesti toimintaan liittyy merkittäviä poliittisia riskejä. Riskit juontuvat sekä sisäisistä että ulkoisistä tekijöistä, joista ulkoiset riskit, kuten lähtö- ja kohdemaiden väliset suhteet sekä laajemmat geopoliittiset dynamiikat, muovaavat ja voimistavat sisäisiä poliittisia riskejä. Erityisesti geopoliittisten riskien havaitaan vaikuttavan merkittävästi eurooppalaisten monikansallisten yritysten T&K-toimintaan Kiinassa kasvavien geopoliittisten jännitteiden, konfliktien ja teknonationalismin myötä. Tästä huolimatta tulokset osoittavat, että ulkomaiset monikansalliset yritykset voivat hyödyntää erilaisia strategioita, keinoja ja työkaluja näiden riskien lieventämiseksi. Näistä poliittiset kyvykkyydet nousevat erityisen keskeisiksi. Lisäksi yrityksen kotimaa, toimiala ja muut yrityskohtaiset ominaisuudet vaikuttavat poliittisten riskien vakavuuteen ja hallittavuuteen, minkä vuoksi osa yrityksistä on muita paremmassa asemassa selviytymään näistä riskeistä. Tutkimus tuottaa uutta tieteellistä tietoa siitä, miten politiikka ja geopolitiikka muovaavat kansainvälistä T&K-toimintaa, miksi osa yrityksistä jatkaa kansainvälistä T&K-toimintaa maissa, joihin liittyy huomattavia poliittisia riskejä sekä miten yritykset voivat vastata T&K-toimintaansa kohdistuviin poliittisiin häiriöihin. Lisäksi tutkimus tarjoaa käytännön arvoa auttamalla yrityksiä tunnistamaan keskeiset poliittiset riskit kansainvälisessä T&K-toiminnassa Kiinassa sekä havainnollistamaan konkreettisia strategioita, keinoja, ja työkaluja, joiden avulla näitä riskejä voidaan lieventää.
Keywords: R&D internationalization, political risks, geopolitical risks, risk management, risk mitigation, China, T&K kansainvälistyminen, poliittiset riskit, geopoliittiset riskit, riskien hallinta, riskien lieventäminen, Kiina